(untitled) (Research, Society and Development, 2024)
Pulmonary tuberculosis represents a significant challenge to public health, especially among young people and adults, due to its impacts on physical health and the social stigma associated with the disease. This study aimed to highlight the challenges associated with the diagnosis and treatment of pulmonary tuberculosis among young people and adults, offering significant insights that can benefit healthcare professionals, researchers, and policymakers. We conducted an extensive literature search in various databases, including BVS, SCIELO, LILACS, and Google Scholar, to identify relevant recent articles. We analyzed 15 selected articles, revealing methodological diversity in addressing the challenges of the disease. We found that 40% of the articles were descriptive studies, 13.33% were cross-sectional studies, 6.6% were quantitative studies, and 40% were qualitative studies. These findings reflect methodological diversity in the analysis of obstacles related to the diagnosis and treatment of the disease, highlighting the impact on public health and the importance of effective preventive and therapeutic strategies. The main challenges include social stigma, limited access to health services, drug resistance, and lack of adherence to treatment. We conclude that integrated and multidisciplinary approaches, along with awareness, facilitated access to health services, continuous research, and effective public policies, are essential to address the challenges associated with this disease.